Practical Application of Assessment Theories for English Teacher through Digital Technologies - Beru Sembiring, Lina Tri Astuty; Sembiring, Shafa Salsabila (ETERNAL (English Teaching Journal), 2024)
Digital technology has revolutionized educational quality, particularly in English as a Foreign Language (EFL) classrooms. This article examines the benefits and challenges of using web-based applications such as Kahoot, Quizizz, Google Apps, and Nearpod for assessments. These tools offer innovative alternatives to traditional methods by enabling dynamic evaluation of student progress, providing real-time feedback, and creating engaging learning experiences. However, challenges such as internet connectivity issues, technological proficiency gaps, and the need for adequate devices can hinder their effectiveness. This paper provides guidelines for optimizing digital assessments, including assessing students' proficiency levels, setting realistic deadlines, ensuring equitable access to technology, and selecting appropriate platforms. The methodology comprises a thorough review and analysis of existing literature on digital tools in EFL classrooms, emphasizing the benefits and challenges of web-based assessment applications. By following these guidelines, educators can design assessments that are valid, reliable, fair, and transparent, thus enhancing teaching strategies and student outcomes. The article also highlights the importance of understanding various assessment types—initial, formative, and summative—and tailoring digital tools to meet specific EFL education objectives. By leveraging digital technologies, educators can improve the assessment process, ultimately contributing to a more effective and successful teaching and learning experience.